Lithium transport by the colon of normal and sodium-depleted rats. - Dolman, D E (1976)
1. The transport of Li by colonic epithelium has been examined in normal and Na-depleted rats. 2. Substitution of Li for Na with lumen of the conon causes the transepithelial electrical potential difference (p.d.) and short-circuit current to fall to low levels and the electrical resistance of fall moderately. Recovery occurs by fairly slowly after removal of Li. 3. Li absorption increases linearly with increasing concentration in the lumen and is significantly faster in Na-depleted rats. Increasing the luminal Na concentration reduces Li absorption from solutions of low Li concentration. 4. Comparison of absorption rates with secretion rates in rats given Li systemically, together with measurements of Li distribution across the epithelium in relationship to the transepithelial p.d. indicate that Li transport is predominatly or entirely passive. Interference with Li absorption by Na suggests, however a mucosal membrane carrier which, since Li absorption rises after Na depletion, may be increased in the Na-depleted state.